Gestational Protein Restriction Increases Cardiac Connexin 43 mRNA levels in male adult rat offspring - Rossini,Kamila Fernanda (2017)
Abstract Background: The dietary limitation during pregnancy influences the growth and development of the fetus and offspring and their health into adult life. The mechanisms underlying the adverse effects of gestational protein restriction (GPR) in the development of the offspring hearts are not well understood. Objectives: The aim of this study was to evaluate the effects of GPR on cardiac structure in male rat offspring at day 60 after birth (d60). Methods: Pregnant Wistar rats were fed a normal-protein (NP, 17% casein) or low-protein (LP, 6% casein) diet. Blood pressure (BP) values from 60-day-old male offspring were measured by an indirect tail-cuff method using an electro sphygmomanometer. Hearts (d60) were collected for assessment of connexin 43 (Cx43) mRNA expression and morphological and morphometric analysis. Results: LP offspring showed no difference in body weight, although they were born lighter than NP offspring. BP levels were significantly higher in the LP group. We observed a significant increase in the area occupied by collagen fibers, a decrease in the number of cardiomyocytes by 104 µm2, and an increase in cardiomyocyte area associated with an increased Cx43 expression. Conclusion: GPR changes myocardial levels of Cx43 mRNA in male young adult rats, suggesting that this mechanism aims to compensate the fibrotic process by the accumulation of collagen fibers in the heart interstitium.